2007
DOI: 10.1039/b615665g
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and binary separation of micro particles for droplet-based digital microfluidics

Abstract: This paper describes a concept of concentration and binary separation of particles and its experimental confirmations for digital microfluidics where droplets are driven by the mechanism of electrowetting-on-dielectric (EWOD). As a fundamental separation unit, a binary separation scheme is developed, separating two different types of particles in one droplet into two droplets, one type each. The separation scheme consists of three distinctive steps, each with their own challenges: (1) isolate two different typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 36 publications
1
81
0
1
Order By: Relevance
“…Cho et al (11) 은 전기적 극성의 입자와 극성이 낮은 입자를 전기영동으로 구분하였으며, Brouzes et al (Fig. 4(a)) 액적 내부의 폴리스타이렌 입자는 나눠진 두 액적 모두에서 퍼 지게 된다.…”
Section: 서 론unclassified
“…Cho et al (11) 은 전기적 극성의 입자와 극성이 낮은 입자를 전기영동으로 구분하였으며, Brouzes et al (Fig. 4(a)) 액적 내부의 폴리스타이렌 입자는 나눠진 두 액적 모두에서 퍼 지게 된다.…”
Section: 서 론unclassified
“…Fundamentals of EWOD, including basic operations on a droplet, 2-4 dynamics of contact angle variation, 5,6 and contact angle saturation 7,8 have been extensively studied. Integrated functional chips 9-11 and in-droplet particle manipulation 12,13 based on EWOD have also been demonstrated. For applications using EWOD, especially in chemical and biochemical fields, efficient mixing of samples and reagents is always desired and is still an issue.…”
Section: Introductionmentioning
confidence: 99%
“…This simultaneous need for control of droplet movement and manipulation of particulate phases inside droplets can be very challenging. Though limited progress has been achieved in this direction, 92,[105][106][107] hybrid tools with their higher degrees of freedom offer significant opportunities in this direction. For example Shah et al 107 demonstrated target separation and individual manipulation of HeLa cell samples by using a combination of EWOD and OET ( Fig.…”
Section: Multi-scale Tools (L Z 10mentioning
confidence: 99%